Present distribution of common dolphin Delphinus delphis in French Mediterranean and adjacent waters as obtained from small boat surveys. (11th December 2018) - Gannier, Alexandre
Abstract: Common dolphin distribution in the western Mediterranean is still poorly known, with the exception of the Alboran Sea. In French waters, the species occurrence is suspected to have strongly decreased during the 20th century. Small boat dedicated surveys from 1988 to 2012 were undertaken to describe common dolphin distribution in five regions of French waters and three southern regions of the western basin. A total survey effort of 38, 561 km resulted in sightings of 25 common dolphin groups in the western basin. Common dolphins were rarely observed off the French continental coast, more frequently around Corsica, and were quite frequent in waters off western Sardinia. Their most favoured habitat was found to be in neritic or upper slope waters. The analysis of stranding records suggested that common dolphins were more abundant in French inshore waters prior to 1980. A major increase of pelagic fish landings occurred from the beginning of the 1960s in the western part of French waters. Local populations of common dolphins may have declined as a consequence of prey depletion.